Resilience and recovery-stress in competitive athletes - García-Secades, X.; Molinero, O.R.; Ruiz-Barquín, R.; Salguero, A.; De la Vega, R.; Márquez, S. (Cuadernos de Psicología del Deporte, 2017)
Resilience is an important construct in sport because athletes must constantly withstand a wide range of stressors to attain optimal performance. e aim of this study was to analyse how the resilient prole inuences the recovery-stress levels of competitive athletes. Participants were 235 subjects (126 males and 109 females, M age = 20.7 years, SD = 4.3) who practiced dierent sports. ey were evaluated on two occasions coinciding with the beginning of the last competitive mesocycle and after the most important competition of the season. Recovery-stress and resilience levels were studied by using the Spanish adaptations of resilience can be dened as the individual skill of keeping performance levels relatively stable, and it can cause positive adaptation in response to exposure to signicant adversity experienced by a given person (García Secades, Molinero, Salguero, Ruiz, de la Vega, & Márquez, 2016). Within this the Recovery-Stress Questionnaire for Athletes (RESTQ-Sport) and the Resilience Scale. Resilience related positively to recovery factors and negatively to stress factors of the RESTQ-Sport. No signicant dierence was observed in resilience scores between evaluations performed during the last mesocycle or competition, but values for the dierent RESTQ-Sport stress factors increased during the second evaluation. Athletes with high resilience attained higher scores in recovery factors and lower scores in stress factors. Our results suggest that a higher level of resilience inuences positively recovery-stress processes.